ATHLETIC IDENTITY AND ACHIEVEMENT GOALS OF GYMNASTICS ATHLETES - Miltiadis Proios (Science of Gymnastics Journal)
The purpose of the present study was to extend knowledge on the relationship between athletic identity and achievement goal orientations. In addition, the present study investigated the impact of independent variables, such as sport divisions and the type of sports gymnastics on the formation of athletic identity. Participants were 140 boys and girls athletes ranging from 8 to 17 years of age (M = 11.86, SD = 2.21), from three sports gymnastics (artistic gymnastics, n = 91; rhythmic gymnastics, n = 37; acrobatic gymnastics, n = 12). The findings of the present study established that the participants exhibit rather high perception of their athletic role, and that such perception is significantly decreased with the increase of sport division. In addition, the above mentioned findings revealed that the degree to which an athlete identifies with the athletic role can be predicted by his/ her predisposition towards achievement goal.